2013
DOI: 10.1149/2.082309jes
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of Anodic Etching of Highly Doped N-type 4H-SiC in Various HF Based Electrolytes

Abstract: In this paper, we study the electrochemical anodization of n-type heavily doped 4H-SiC wafers in HF based electrolytes without any UV light assistance. We present, in particular, the differences observed when varying the process conditions such as the HF concentration, the type of additive and the applied current regime. The use of a solvent such as acetic acid seems to be more suitable to produce homogeneous morphologies compared with Cetyltrimethylammonium chloride (CTAC), Ammonium dodecylsulfate (ADS), Trit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…The SiC etching mechanism proposed by Shor and Kurtz 16 has been generally accepted. 13,[17][18][19][20][21][22][23] According to their hypothesis, anodic etching of SiC in aqueous HF occurs in two steps: oxidation of SiC and dissolution of the formed oxide. They suggested that oxidation of SiC occurs via the following reactions: 16 SiC…”
Section: Methodsmentioning
confidence: 99%
“…The SiC etching mechanism proposed by Shor and Kurtz 16 has been generally accepted. 13,[17][18][19][20][21][22][23] According to their hypothesis, anodic etching of SiC in aqueous HF occurs in two steps: oxidation of SiC and dissolution of the formed oxide. They suggested that oxidation of SiC occurs via the following reactions: 16 SiC…”
Section: Methodsmentioning
confidence: 99%
“…Electrochemical etching (ECE) is an oxidation/oxide removal process obtained by dipping silicon carbide samples in an HF solution and electrically supplying holes for the oxidation through the back metal contact (Dahal et al, 2017;Watanabe et al, 2011;Gautier et al, 2012Gautier et al, , 2013. The process is capable of removing highly doped (!1 Â 10 18 cm À3 ) p-type and n-type layers but is selective towards low-doped n-type layers (selectivity !…”
Section: Device Fabricationmentioning
confidence: 99%
“…The substrate removal was obtained by electrochemical etching. ECE is an oxidation/oxide-removal process obtained by dipping the SiC wafer in a hydrofluoridric acid-based solution and electrically supply holes for the oxidation through a 100 nm aluminium back metal contact [6,[21][22][23]. The process is capable of removing highly doped (≥ 10 18 cm −3 ) p-type and n-type layers but is selective towards low-doped n-type layers (selectivity > 1000:1 with respect to the 5 × 10 13 cm −3 doped n − layer).…”
Section: Sample Preparationmentioning
confidence: 99%